2022
DOI: 10.3390/ma15103699
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Performance of High-Entropy Coatings (HECs): A Review

Abstract: Surface coatings that operate effectively at elevated temperatures provide compatibility with critical service conditions as well as improved tribological performance of the components. High-entropy coatings (HECs), including metallic, ceramics, and composites, have gained attention all over the world and developed rapidly over the past 18 years, due to their excellent mechanical and tribological properties. High-entropy alloys (HEAs) are defined as alloys containing five or more principal elements in equal or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 191 publications
(253 reference statements)
0
4
0
Order By: Relevance
“…The system, which holds up the rotating shaft, comprises a top and a bump foil. The top foil and the journal, which are in touch with the shaft when it is stationary, are separated by a thin layer or gap when moving at higher speeds because of hydrodynamic pressure [69]. As a result, the bearing strikes the race at a slow rate during startup acceleration at standard temperature and shutdown deceleration at high temperature.…”
Section: Operating At Severe Working Eventsmentioning
confidence: 99%
“…The system, which holds up the rotating shaft, comprises a top and a bump foil. The top foil and the journal, which are in touch with the shaft when it is stationary, are separated by a thin layer or gap when moving at higher speeds because of hydrodynamic pressure [69]. As a result, the bearing strikes the race at a slow rate during startup acceleration at standard temperature and shutdown deceleration at high temperature.…”
Section: Operating At Severe Working Eventsmentioning
confidence: 99%
“…This elemental composition seems to promote high configurational entropy and the formation of BCC phases. The correlation between the top five RHEAs and the BCC crystal structure hints at high hardness, translating into low wear rates [26]. These findings strongly support the idea that the top-ranked RHEAs excel in wear resistance, making them highly suitable for use as coating materials for hot-forging dies, which is evident in the WMoTaNb RHEA, which has a BCC crystal structure and exhibits a relatively high wear resistance (or low wear rate) at ambient and elevated temperatures [60].…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Die coatings can be categorized into three main groups [18,19,21]: metallic coatings (comprising transition metals, refractory metals, and lightweight metals), ceramic coatings (encompassing oxides, borides, carbides, and nitrides), and composite coatings (involving ceramic-reinforced and hybrid coatings). Upon careful evaluation, it becomes evident that refractory HEAs (RHEAs) exhibit exceptional suitability as coatings for conventional hot forge die materials, offering a remarkable combination of properties ideally suited for their intended application as coatings on hot forge dies, employing various coating techniques [19,[21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has suggested that materials possessing favorable mechanical qualities, such as high hardness, elastic modulus, and fracture toughness, can lead to improved tribological performance in various applications [7,8]. High-entropy alloys (HEAs), a recent advancement in alloy development, have garnered considerable interest due to their potential properties [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%